Osteopontin Is Upregulated in Human and Murine Acute Schistosomiasis Mansoni - Pereira, Thiago Almeida (PLoS Negl Trop Dis, 2016)
BACKGROUND: Symptomatic acute schistosomiasis mansoni is a systemic hypersensitivity reaction against the migrating schistosomula and mature eggs after a primary infection. The mechanisms involved in the pathogenesis of acute schistosomiasis are not fully elucidated. Osteopontin has been implicated in granulomatous reactions and in acute hepatic injury. Our aims were to evaluate if osteopontin plays a role in acute Schistosoma mansoni infection in both human and experimentally infected mice and if circulating OPN levels could be a novel biomarker of this infection. METHODOLOGY/PRINCIPAL FINDINGS: Serum/plasma osteopontin levels were measured by ELISA in patients with acute (n = 28), hepatointestinal (n = 26), hepatosplenic (n = 39) schistosomiasis and in uninfected controls (n = 21). Liver osteopontin was assessed by immunohistochemistry in needle biopsies of 5 patients. Sera and hepatic osteopontin were quantified in the murine model of schistosomiasis mansoni during acute (7 and 8 weeks post infection, n = 10) and chronic (30 weeks post infection, n = 8) phase. Circulating osteopontin levels are increased in patients with acute schistosomiasis (p = 0.0001). The highest levels of OPN were observed during the peak of clinical symptoms (7–11 weeks post infection), returning to baseline level once the granulomas were modulated (>12 weeks post infection). The plasma levels in acute schistosomiasis were even higher than in hepatosplenic patients. The murine model mirrored the human disease. Macrophages were the major source of OPN in human and murine acute schistosomiasis, while the ductular reaction maintains OPN production in hepatosplenic disease. Soluble egg antigens from S. mansoni induced OPN expression in primary human kupffer cells. CONCLUSIONS/SIGNIFICANCE: S. mansoni egg antigens induce the production of OPN by macrophages in the necrotic-exudative granulomas characteristic of acute schistosomiasis mansoni. Circulating OPN levels are upregulated in human and murine acute schistosomiasis and could be a non-invasive biomarker of this form of disease.